2006
DOI: 10.1002/ijc.21791
|View full text |Cite
|
Sign up to set email alerts
|

Associations between vitamin D, vitamin D receptor gene and the androgen receptor gene with colon and rectal cancer

Abstract: The transcriptional activity of the vitamin D receptor (VDR) gene is regulated, at least in part, by the androgen receptor (AR) gene. We evaluate how the number of polyglutamine (CAG) repeats of the AR gene influence colorectal cancer in conjunction with vitamin D, sunshine exposure and VDR. Studies of colon (1,580 cases and 1,968 controls) and rectal (797 cases and 1,016 controls) cancer were used. Vitamin D intake and average hours of sunshine exposure interacted with AR genotype in men. Men with low vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 41 publications
(49 reference statements)
0
28
1
Order By: Relevance
“…We studied 550 patients with colorectal cancer without somatic alterations in CAG repeats, and demonstrated that long CAG repeats of the AR genotype were associated with higher (1.293-fold in males, 1.255-fold in females, and 1.277-fold in total colorectal cancer population, respectively) risk for colorectal cancer in a Chinese population, whereas a short CAG repeat sequence may provide a certain degree of protection against colorectal cancer. Our study was different from that of Slattery and colleagues (13), who found that the AR genotype can decrease the risk for rectal cancer between patients and controls if the genotype possesses a short CAG repeat length. We also obtained a different cut-off point of CAG repeat length, which might attribute to different regions and ethnicities.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We studied 550 patients with colorectal cancer without somatic alterations in CAG repeats, and demonstrated that long CAG repeats of the AR genotype were associated with higher (1.293-fold in males, 1.255-fold in females, and 1.277-fold in total colorectal cancer population, respectively) risk for colorectal cancer in a Chinese population, whereas a short CAG repeat sequence may provide a certain degree of protection against colorectal cancer. Our study was different from that of Slattery and colleagues (13), who found that the AR genotype can decrease the risk for rectal cancer between patients and controls if the genotype possesses a short CAG repeat length. We also obtained a different cut-off point of CAG repeat length, which might attribute to different regions and ethnicities.…”
Section: Discussioncontrasting
confidence: 99%
“…Primers (13) were AR-Forward 5 0 -GTTTCTGTGGGGCCTCTAC-GATGG-3 0 and AR-Reverse 5 0 -GTTTCTGCGCGAAGTGATCCA-GAA-3 0 . AR-Forward was fluorescently labeled with 6-carboxyfluorescine (FAM).…”
Section: Pcr-based Genescan Analysis Of Ar Cag Repeats Lengthmentioning
confidence: 99%
“…Interactions between the VDR gene and other genes have also been suggested. For instance, the androgen receptor gene could interact with the Fok1 VDR polymorphism and the sunlight exposure and vitamin D intake (62).…”
Section: Discussionmentioning
confidence: 99%
“…3). Several investigations reported that the gene VDR and FOK1 FF genotype with respect to the higher vitamin D consumption reduces the risk of colon cancer (45), breast cancer (46), and skin cancer (47) among women. Our study suggests that interactions between FOK1 polymorphism in Iranian obese women and dietary intake of calcium and vitamin D play a major role in bone mineral density and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%